The impact of school in hospital sabahwomen and children’s hospital volunteer program - Datu Bandira, Puteri Nurul Nazahiah; Yasis, Rosmini (Jurnal Pendidikan Bitara UPSI, 2019)
The School In Hospital strives to provide formal education through fun learning approach to students receiving treatment at 15 hospitals throughout the nation. The School In Hospital (SIH) Sabah Women and Children’s Hospital (SWACH) has a Volunteer Program in which NGOs and CSR initiatives could participate in. Examining the impact of the volunteer program is crucial to ensure that the volunteer activities are in line with the mission of the school. This will also provide the school with information that will be useful for future improvements in the volunteer program. Thematic analysis was done on the volunteers’ reflective writing in the volunteer task sheet and on the teachers’ focus group interview. The analysis reveals that the SIH SWACH volunteer program has had a positive impact on both the volunteers themselves and the students.  Thus, the involvement of NGOs and CSR initiatives in the volunteer program is considered complementary to the mission of the school, especially through the volunteer activities they conduct. An area of improvement related to implementation of the volunteer program has also been identified.